Impact of COVID-19 on the Health Response to Family Violence in Aotearoa New Zealand: A Qualitative Study - Jane Koziol-McLain PhD, RN; Christine Cowley BSW, EN; Shoba Nayar PhD, NZROT; Diane Koti MA, DHlth (Candidate) (SAGE Publishing, 2023)
COVID-19 pandemic planning and response has resulted in unprecedented upheaval within health systems internationally. With a concern for increasing frequency and escalation of family violence, the so called "shadow pandemic," we wondered how health system violence intervention programs were operating during this time. In Aotearoa New Zealand, the Ministry of Health Violence Intervention Program (VIP), using a systems approach, seeks to reduce and prevent the health impacts of family violence and abuse through early identification, assessment, and referral of victims presenting to designated health services. In this qualitative descriptive study, we explored how the VIP program was impacted during the first year of the COVID-19 pandemic. Forty-one VIP coordinators and managers representing 15 of the 20 New Zealand District Health Boards and the National VIP Team participated. Across 12 focus groups (8 face to face and 4 via Zoom) and 7 individual interviews (all via Zoom) participants shared their experience navigating systems to support frontline health providers' responsiveness to people impacted by family violence during the pandemic. In our reflexive thematic analysis, we generated 3 themes: Responding to the moment, valuing relationships, and reflecting on the status quo. Our findings demonstrate the dynamic environment in which participants found creative ways to adapt to the uncertainty and engage with communities to re-shape interventions and ensure continued implementation of the program. At the same time, challenges within the system prior to the pandemic were brought into view and highlighted the need for action. These included, for example, the need for improved engagement with Māori (Indigenous people of Aotearoa New Zealand) to address long-standing health inequities. Having quality essential services for those impacted by family violence that engages with local knowledge and networks and routinely copes with uncertainty will strengthen our systems to minimize risk of harm during emergencies.